Assessing the stability of azopolymer nanotopography during live-cell fluorescence imaging - Abdelrahman, Mona H.; Shen, Jerry; Fisher, Nicholas C.; Losert, Wolfgang; Fourkas, John T. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Photomodifiable azopolymer nanotopographies represent a powerful means of assessing how cells respond to rapid changes in the local microenvironment. However, previous studies have suggested that azopolymers are readily photomodified under typical fluorescence imaging conditions over much of the visible spectrum. Here we assess the stability of azopolymer nanoridges under 1-photon and 2-photon imaging over a broad range of wavelengths. Methods Azopolymer nanoridges were created via microtransfer molding of master structures that were created using interference lithography. The effects of exposure to a broad range of wavelengths of light polarized parallel to the ridges were assessed on both a spinning-disk confocal microscope and a 2-photon fluorescence microscope. Experiments with live Dictyostelium discoideum cells were also performed using alternating cycles of 514-nm light for photomodification and 561-nm light for fluorescence imaging. Results and Discussion We find that for both 1-photon and 2-photon imaging, only a limited range of wavelengths of light leads to photomodification of the azopolymer nanotopography. These results indicate that nondestructive 1-photon and 2-photon fluorescence imaging can be performed over a considerably broader range of wavelengths than would be suggested by previous research.